Patient-Reported Outcome Measure Collection for TKA: What Surgeons Need to Know - Geiselmann, Matthew T.; Whittaker, Mathew J.; Scuderi, Giles R. (The Journal of Knee Surgery, 2025)
As the population ages and the prevalence of knee osteoarthritis increases, total knee arthroplasty (TKA) is expected to grow in demand. Traditionally, the success of TKA has been measured through clinical assessments, imaging, and the incidence of postoperative complications. Over the past decade, patient-reported outcome measures (PROMs) have become crucial in evaluating clinical outcomes. PROMs are soon to be tied to financial incentives in value-based payment programs as a measure of the quality of care provided. Centers for Medicare and Medicaid Services (CMS) has implemented a nationwide policy to enhance and standardize the collection of PROMs for those undergoing total joint arthroplasty. The policy is titled Patient Reported Outcome based Performance Measure or “PRO-PM.” This requires mandatory reporting in 2025, and by 2028, hospital payment evaluations will incorporate this data. CMS will require hospitals to achieve at least 50% postoperative PROM collection rates to qualify for full annual payment in 2028. Providers are incentivized to improve scores on PROMs, such as pain levels and physical function after procedures, as higher PROM scores often correlate with better reimbursement rates under these programs. Recent advancements in interactive technology, including mobile apps and telemedicine platforms, have enabled the collection of PROMs from patients without requiring or prior to a clinic visit. Looking ahead, the mandatory PROM reporting requirements set by the CMS highlight the urgency of adopting scalable, technology-driven solutions. Literature suggests women, individuals with lower socioeconomic status, lower educational attainment, and non-English speakers have significantly lower PROM response rates. While these mandates aim to standardize care quality, they also risk exacerbating disparities if underserved populations face barriers to participation. Equity-focused strategies, alongside continued investment in technology, will be critical to achieving widespread adoption and maximizing the benefits of PROMs in TKA care. Ultimately, the integration of electronic and adaptive PROM systems has the potential to transform the TKA landscape, offering a model for leveraging technology to enhance patient engagement, optimize care delivery, and improve outcomes across diverse populations.
Keywords: total knee arthroplasty; patient-reported outcome measures; total joint; arthroplasty